Ecology of Rafflesia arnoldii (Rafflesiaceae) in Pandam Gadang West Sumatra - Syafroni Pranata; Sulistijorini Sulistijorini; Tatik Chikmawati (Journal of Tropical Life Science, 2019)
Pandam Gadang has tropical forests which become the habitat of Rafflesia (Rafflesia arnoldii) which grows as a parasite of Tetrastigma (Vitaceae). Study on R. arnoldii is needed since its population continuously decrease as a result of habitat destruction of its host. The aim of the study was to determine habitat conditions, vegetation structure, and characteristic of the host species of Rafflesia; to identify environmental factors, and determine the Rafflesia habitat suitability in Pandam Gadang Koto Tinggi Village, West Sumatra. Analysis of vegetation in the habitat where Rafflesia grows using a circular plot. The number of individuals Rafflesia found was recorded and completed with observations of its morphology. Micro-climate measurements were carried out together with data collection in the field. Flower morphological analysis was descriptively presented. Environmental parameters were-processed with Canoco software 4.56 using Canonical Correspondence Analysis. Habitat suitability was analyzed using Maximum Entropy. The 17 Rafflesia individuals found on Pandam Gadang were R. arnoldii, known as "Cendawan Biriang", living parasitically on Tetrastigma leucostaphylum. The results of analysis of vegetation in the Rafflesia habitat showed that there were 250 individual plants consisting of 42 species and 21 genera. Seedlings most dominant was Lauraceae, belt were dominated by Moraceae, Meliaceae, and Euphorbiaceae. Trees were dominated by Euphorbiaceae, Moraceae, and Meliaceae. Existence and survival of R. arnoldii depended on soil pH 7-7.8, environmental humidity 83-91.8 % and distance from the nearest river 3-27.8 m.